2004
DOI: 10.1111/j.1474-9728.2004.00103.x
|View full text |Cite
|
Sign up to set email alerts
|

Stress responses and innate immunity: aging as a contributory factor

Abstract: SummaryEvolutionary pressure has selected individuals with traits that allow them to survive to reproduction, without consideration of the consequences for the post-child rearing years and old age. In the 21st century, society is populated increasingly by the elderly and with the falling birth rate and improved health care this trend is set to continue for the foreseeable future. To minimize the potential burden on health services one would hope that 'growing old gracefully' should also mean 'growing old healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
104
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 136 publications
(109 citation statements)
references
References 118 publications
3
104
0
2
Order By: Relevance
“…adipose tissue and immune cells (25). Indeed, our own in vitro data have shown that DHEAS can overcome the suppressive effects of cortisol upon immune cell function, specifically the generation of superoxide by neutrophils (15), supporting the proposal that it is the ratio of these two hormones that will determine biological outcome in vivo (26). Moreover, there are no reports of MetS suppressing DHEAS production, supporting the notion that the direction of causality is from a lower ratio to MetS.…”
Section: Discussionmentioning
confidence: 75%
“…adipose tissue and immune cells (25). Indeed, our own in vitro data have shown that DHEAS can overcome the suppressive effects of cortisol upon immune cell function, specifically the generation of superoxide by neutrophils (15), supporting the proposal that it is the ratio of these two hormones that will determine biological outcome in vivo (26). Moreover, there are no reports of MetS suppressing DHEAS production, supporting the notion that the direction of causality is from a lower ratio to MetS.…”
Section: Discussionmentioning
confidence: 75%
“…It has long been appreciated that the inhibition of leptin signaling that results from the mutations in the ob/ob mice and db/db mice leads to an elevation of CORT levels, which in turn have been linked to the suppression of inflammatory responses (Butcher and Lord, 2004;Fiuza and Suffredini, 2001). Therefore, it is important to note that accompanying the reduced blood glucose and lipid-lowering effect, darglitazone significantly decreased the CORT level in both control and diabetic ob/ob mice after 4 h of H/I recovery, but this effect was lost at later time points of H/I recovery.…”
Section: Discussionmentioning
confidence: 99%
“…With the increasing evidence that inflammation plays an important role in age-related cognitive decline and dementia, there has been a recent surge in interest in inflammatory biomarkers (Butcher & Lord, 2004). Several studies have found that inflammatory markers, such as interleukin-6 (IL-6), interleukin-12 (IL-12), tumor necrosis factor-a (TNFa), and C-reactive protein (CRP), are elevated in the elderly and are associated with cognitive impairment and decline (Licastro et al, 2000;Engelhart et al, 2004;Dimopoulos et al, 2006;Alvarez et al, 2007;Zuliani et al, 2008;Trollor et al, 2011), as well as increased risk of mortality .…”
Section: Introductionmentioning
confidence: 99%